Quasar outflows at z ≥ 6: the impact on the host galaxies. Issue 3 (5th October 2017) - Barai, Paramita; Gallerani, Simona; Pallottini, Andrea; Ferrara, Andrea; Marconi, Alessandro; Cicone, Claudia; Maiolino, Roberto; Carniani, Stefano
Abstract: We investigate quasar outflows at z ≥ 6 by performing zoom-in cosmological hydrodynamical simulations. By employing the smoothed particle hydrodynamics code gadget -3, we zoom in the 2 R 200 region around a 2 × 10 12 M⊙ halo at z = 6, inside a (500 Mpc) 3 comoving volume. We compare the results of our active galactic nuclei (AGN) runs with a control simulation in which only stellar/SN feedback is considered. Seeding 10 5 M⊙ black holes (BHs) at the centres of 10 9 M⊙ haloes, we find the following results. BHs accrete gas at the Eddington rate over z = 9–6. At z = 6, our most-massive BH has grown to M BH = 4 × 10 9 M⊙ . Fast ( v r > 1000 km s −1 ), powerful (M_out 2000 M_ yr −1 ) outflows of shock-heated low-density gas form at z ∼ 7, and propagate up to hundreds kpc. Star formation is quenched over z = 8–6, and the total star formation rate (SFR surface density near the galaxy centre) is reduced by a factor of 5 (1000). We analyse the relative contribution of multiple physical process: (i) disrupting cosmic filamentary cold gas inflows, (ii) reducing central gas density, (iii) ejecting gas outside the galaxy; and find that AGN feedback has the following effects at z = 6. The inflowing gas mass fraction is reduced by ∼ 12 per cent, the high-density gas fraction is lowered by ∼ 13 per cent, and ∼ 20 per cent of the gas outflows at a speed larger than the escape velocity (500 km s −1 ). We conclude that quasar-host galaxies at z ≥ 6 are accreting non-negligible amount of cosmic gas, nevertheless AGN feedback quenches their star formation dominantly by powerful outflows ejecting gas out of the host galaxy halo.